Identification of mannose-binding lectin as a mechanism in progressive immunoglobulin A nephropathy - Shi, Beili (Int J Clin Exp Pathol, 2015)
Immunoglobulin A nephropathy (IgAN), the pathogenesis of which remained still unclear is one of the leading courses of end-stage renal disease in approximately 50% affected patients. On the basis of several researches, the activation of complement mannose-binding lectin (MBL) pathway might be the underlying mechanism in disease progress. In order to investigate the relationship between MBL pathway and IgAN, we discussed the MBL gene polymorphism as well as its expressed level in serum, urine and renal parenchymal, with renal outcome in IgAN patients. The significantly down-regulated expression of MBL was discovered, which may serve as a potential urinary biomarker in progressive IgAN according to the results of difference in gel electrophoresis and matrix-assisted laser desorption/ionization time of flight mass spectrometry. The single nucleotide polymorphisms of MBL gene in promoter and exon region were found and confirmed relating with the poor prognosis of progressive IgAN patients. As a result, the deficient activation of MBL pathway caused by the mutation of MBL accompanied with low expressed level of MBL in serum might be the potential inspiring regulation in IgAN, and will attract a promising insight in remedy of IgAN to inhibit further progress.